PENGEMBANGAN MEDIA PAPAN KARTU BERGAMBAR PADA PEMBELAJARAN TEMATIK MUATAN PPKN SISWA KELAS II SD - Diana, Mega Wikan; Chairiyah, Chairiyah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This study aims to produce a learning media product "Picture Card Board" on the thematic learning content of PPKN. This type of research is research and development with development procedures according to Borg and Gall. The study population was all students of class II SDN Gayamharjo totaling 27 students, all class II students of SDN Dadapsari totaling 5 students, and all grade III students of SDN Dadapsari totaling 6 students. Data collection techniques employing observation, interviews with class II teachers, and questionnaires to determine the situation during the learning process. The data analysis technique used quantitative descriptive statistics. The results of this study indicate that the picture cardboard media can be declared fit for use. The percentage of material validation results from the lecturer shows the number 84% with the criteria suitable for use. The percentage of validation results from grade II teachers at SDN Gayamharjo shows many 92% and the validation of grade II teachers at SDN Dadapsari shows many 92% with the same criteria which is suitable for use. For the percentage of media validation results from lecturers, it shows the number 91% with the criteria suitable for use. The percentage of media validation results from grade II teachers at SDN Gayamharjo shows many 95% and from grade II teachers at SDN Dadapsari shows a figure of 94% with the criteria suitable for use. Meanwhile, the percentage results at the time of the initial field trial showed that the number was 91% with the criteria category suitable for use, at the time of the main field trial it obtained a percentage of 93% with the criteria suitable for use, and during the operational field trial, the percentage value was 89% with criteria worthy of use.